Effects of web accessibility on search engines and webometrics ranking - Ayu, Media Anugerah; Elgharabawy, Mohamed Ahmed (IGI Global, 2013)
Previous researches have highlighted the importance of web accessibility of a website. Its importance has made the W3C (World Wide Web Consortium) come up with Web Content Accessibility Guidelines (WCAG) as a guideline for developing an accessible website. Amongst websites available in the web wide world, many of them are fall under the education institution website category. These education institution websites are mostly the first door that people will go to visit to get information about education services and courses provided by the institution. Thus, to be accessible is an essential issue for these websites. Another issue that gets much attention in the current competitive internet world is to be visible by popular search engines and ranked at their top lists. For higher learning institutions there is an online ranking that they like to be in the top list, i.e. Webometrics. This paper attempts to address those two issues of web accessibility and being at the top list. It presents a study that investigates whether web accessibility has a contributing effect to ranking position in Webometrics and popular search engines. The research covers websites from higher learning institutions and education domains. Three popular search engines are used in this research, i.e. Google, Yahoo! and Bing. The study produces interesting results that would be useful as a guide for higher learning institutions that want to improve their online ranking.